Biofilms, infection and antimicrobial therapy - Pace, John L. (Taylor & Francis, 2006)
Providing general understanding of issues in antimicrobial research, Biofilms, Infection, and Antimicrobial Therapy supplies an excellent overview of the economic burden associated with treating biofilm-related infections. It includes a discussion of cutting-edge aspects in the area of antibacterial tolerance and resistance, describes animal models essential for identification of new effective therapeutic regimens, and examines the effectiveness of various antimicrobial agents for therapy of associated infections. Biofilms, Infection, and Antimicrobial Therapy contains detailed protocols to aid physicians in the treatment of these refractory and often difficult-to-manage infections.